Integrating Product Innovation and Sustainable Packaging to Enhance Competitiveness of Dodol SMEs - Kurniawan, Wawan; Harahap, Elfira Febriani; Busnetty, Ida; Pangestu, Rama; Cristina, Meily (Penerbit Widina, Widina Media Utama, 2025)
Dodol Betawi, a traditional Indonesian confection, faces limited competitiveness due to its high sugar content, lack of product diversification, and reliance on plastic packaging. These challenges reduce consumer appeal, restrict entry into modern retail channels, and hinder export readiness. This study reports a participatory community service program with UMKM D’Tungku in Bojonggede, West Java, aimed at developing a replicable model that integrates product innovation, appropriate technology, and sustainable packaging. Five low-sugar dodol variants enriched with local botanicals—pumpkin, pineapple, pandan leaves, hibiscus, and butterfly pea—were formulated to provide functional benefits such as dietary fiber, antioxidants, and potential anti-diabetic properties. Alongside product reformulation, eco-friendly packaging prototypes were introduced using bamboo, natural leaves, and linen pouches to replace single-use plastics. A preliminary sensory evaluation involving SME workers indicated strong acceptance for color, taste, and aroma, though texture improvements remain necessary. Packaging innovations were well-received for their aesthetics and sustainability, despite higher production costs compared to plastic alternatives. Furthermore, appropriate technology in the form of mixing and rolling machines improved efficiency and ensured consistent product size, reducing processing time from four hours to one and a half hours. Initial export activities through the Indonesian diaspora in Japan confirmed international interest in Dodol Betawi, while underscoring the importance of sustainable packaging to meet environmentally conscious consumer expectations. The findings highlight that integrating nutritional innovation, technology adoption, and eco-friendly design provides a holistic and scalable strategy for enhancing SME competitiveness, preserving cultural food heritage, and strengthening readiness for global markets.ABSTRAKDodol Betawi sebagai pangan tradisional Indonesia menghadapi keterbatasan daya saing akibat tingginya kandungan gula, minimnya diversifikasi produk, serta ketergantungan pada kemasan plastik. Tantangan ini menurunkan daya tarik konsumen, membatasi akses ke saluran ritel modern, dan menghambat kesiapan ekspor. Penelitian ini melaporkan program pengabdian masyarakat partisipatif bersama UMKM D’Tungku di Bojonggede, Jawa Barat, yang bertujuan mengembangkan model replikasi melalui integrasi inovasi produk, teknologi tepat guna, dan kemasan berkelanjutan. Lima varian dodol rendah gula diperkaya bahan botani lokal labu kuning, nanas, daun pandan, kembang sepatu, dan bunga telang diformulasikan untuk memberikan manfaat fungsional seperti serat pangan, antioksidan, dan potensi antidiabetes. Sejalan dengan reformulasi produk, prototipe kemasan ramah lingkungan diperkenalkan menggunakan bambu, daun alami, dan pouch linen sebagai pengganti plastik sekali pakai. Evaluasi sensoris awal yang melibatkan pekerja UMKM menunjukkan penerimaan positif terhadap warna, rasa, dan aroma, meskipun tekstur masih memerlukan perbaikan. Inovasi kemasan diterima baik dari aspek estetika dan keberlanjutan, meski menghadapi tantangan biaya lebih tinggi dibanding plastik. Selain itu, penerapan teknologi tepat guna berupa mesin pengaduk dan pelinting meningkatkan efisiensi dan konsistensi ukuran produk, serta memangkas waktu produksi dari empat jam menjadi satu setengah jam. Upaya ekspor awal melalui diaspora Indonesia di Jepang membuktikan adanya minat pasar internasional, sekaligus menegaskan pentingnya kemasan berkelanjutan untuk memenuhi ekspektasi konsumen yang peduli lingkungan. Temuan ini menegaskan bahwa integrasi inovasi gizi, adopsi teknologi, dan desain ramah lingkungan merupakan strategi holistik dan terukur untuk meningkatkan daya saing UMKM, melestarikan warisan kuliner, dan memperkuat kesiapan memasuki pasar global.